SURVIVAL ANALYSIS FOR CLINICAL STUDIES - Langova, Katerina (Biomedical papers, 2008)
AIM: This paper focuses on the use of censored data in survival analysis. Survival analysis is used most frequently in the case of cancer patients when the study is finished and a number of individuals are still alive. The original article cited2 was declared recently to be the most cited statistical study in the biomedical area. The goal of this paper is to explain the basic principles and methods involved. The way survival analysis processes data and interprets outputs is presented using the clinical data of oncological patients.METHODS AND RESULTS: Survival analysis is used to estimate survivor function from survival data, to compare survivor functions and to assess the relationship of explanatory variables to survival time. These methods were applied to the data of 176 patients with heamato-oncological diagnoses who had undergone bone marrow blood transplant.CONCLUSION: It is very important to use appropriate methods when processing statistical data. Standard statistical procedures used for incomplete data could not provide the correct estimation.
Keywords: Survival analysis/Censored data/Kaplan-Meier survival curves/Cox proportional hazards model